Editorial - Cock, Ian E. (Pharmacognosy Communications)
Dear Readers and Authors,I am pleased to bring you Volume 13, Issue 2 of Pharmacognosy Communications. In this issue, we present an evaluation of the antibacterial activity of Eclipta prostrata (L.) L. (commonly known as Bringaraja and false daisy) against selected bacterial triggers of autoimmune inflammatory diseases. We also present a study that evaluates the ability of Hamamelis virginiana L. extracts to potentiate the growth inhibitory effects of the antibiotic ciprofloxacin in Pseodomonas aeruginosa infections. Finally, another study examines the antibacterial activity and toxicity of Jacksonia scoparia R.Br. (commonly known as dogwood) leaf extracts.